Scientific opinion of Flavouring Group Evaluation 503 (FGE.503): grill flavour 'Grillin' CB‐200SF'. (8th September 2017) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Chipman, Kevin; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) was requested to deliver a scientific opinion on the implication for human health of the product Grillin' CB‐200SF [FL‐no: 21.004] in the Flavouring Group Evaluation 503, according to Regulation (EC) No 1331/2008 and Regulation (EC) No 1334/2008 of the European Parliament and of the Council. The product is derived from heat‐treated high oleic sunflower oil, and intended to be used as a food flavouring with charbroiled or grilled aroma in a wide variety of food categories either in liquid or powder form. Information on manufacturing and compositional data was considered adequate to show the reproducibility of the production process. However, the Panel noted that a substantial amount of the non‐volatile fraction of the product could not be identified. The chronic dietary exposure to the substance estimated using the Added Portions Exposure Technique (APET) was calculated to be 60 mg/person per day for a 60‐kg adult and 37.8 mg/person per day for a 15‐kg child. The data submitted for evaluating the genotoxic potential of the flavouring was considered insufficient. There are still eight substances in the flavouring for which the evaluation of genotoxic potential is pending. No toxicity studies have been provided on the final product itself. Only information on a number of constituents of the flavouring and data on toxicity of several thermally treated fats and oils were provided by the applicant. However, the Panel considered the time–temperature conditions that were applied in the preparation of the substances tested as not comparable to those applied in the course of the production of the flavouring. The Panel concluded that on the basis of the data provided by the applicant the safety of Grillin' CB‐200SF cannot be established.